The Institution of Civil Engineers and the Institution of Highway Engineers national conference on maintenance and reconstruction of motorways and other heavily trafficked roads Royal Spa Centre, Leamington Spa, Warwickshire, Septemebr 25th 1980. (Thomas Telford, 1980)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a national conference held in Leamington Spa in conjunction with the Institution of Highway Engineers on 25 September 1980.